Level of knowledge and skills on chronic complications of diabetes mellitus 2, hospital national PNP Luis N. Saenz, 2016: Nivel de conocimientos y aptitudes sobre complicaciones crónicas de la diabetes mellitus 2, hospital nacional PNP. Luis N. Saenz, 2016 - Calderón-Rivera, Aldo Juvenal (2019)
Objective: To determine the relationship between knowledge and skills in diabetic patients on theChronic complications of diabetes mellitus 2 in the Endocrinology Service of the PNP National HospitalLuis N. Suárez in 2016. Methods: Quantitative, descriptive, cross-sectional and correlational study. They were surveyedto 110 diabetic patients with a questionnaire to assess knowledge (10 items with response frommultiple selection) and another for skills (modified Lickert type). The knowledge was classifiedas high, medium and low level and the aptitudes as favorable, unfavorable and indifferent according to the Scale of Estanones. The normality of the scores was determined with the Kolmogorov-Smirnov Test and theassociations with chi square, p <0.05 and Pearson's correlation test. Results: The average age was49.85 ± 6.97 years, 74.5% female, 75.5% with sick time between 1-5 years, 67.3% with goodadherence to pharmacological treatment. The level of knowledge was: high 28.2%, medium 49.1% and low 22.7%, and the skills were: favorable 23.6%, unfavorable 58.2% and indifferent 18.2%. There is no relationship between knowledge and skills (p = 0.247). Only statistical association was found between knowledge and pharmacological treatment (p <0.05). Conclusion: Diabetic patients have a level of knowledge about his chronic complications and his aptitudes were predominantly unfavorable. It is necessary to perform educational strategies to improve the knowledge and skills of diabetics. Keywords: Chronic complications; Diabetes mellitus 2; Knowledge; Aptitudes; Correlation. (source: DeCS BIREME).   DOI:  10.25176/RFMH.v19.n1.1793